Perspectives and Socioeconomic Influences of Personal Protective Equipment Waste Management on Post-COVID-19 - Suhardono, Sapta; Septiariva, Iva Yenis; Mulyana, Rachmat; Suryawan, I Wayan Koko; Ulhasanah, Nova; Prayogo, Wisnu; Sari, Mega Mutiara (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The COVID-19 pandemic brought an upsurge in Personal Protective Equipment (PPE) usage, leading to emergent challenges in its post-use management, especially in urban centers like Jakarta. This study conducted a quantitative exploration, employing simple random sampling techniques, to investigate Jakarta citizens; perceptions of PPE waste management. Two significant factors,